INDUKSI KALUS EMBRIOGENIK DAN EMBRIO SOMATIK DARI EKSPLAN DAUN KULIM (Scorodacarpus borneensis Becc.) - Yelnititis Yelnititis (Jurnal Pemuliaan Tanaman Hutan, 2020)
Kulim is one of woody plant that have multifunction as wood source and for spice and medicinal. Generative propagation of this plant have trouble because seed use limited. The use of leaf segment through somatic embryogenesis to solve the problem. The objective of this study is to obtain the best treatment to embryogenic callus induction. The modification of basal medium of Murashige and Skoog was used as growth medium. The experiment was conducted in three stages are callus induction, embryogenic callus and somatic embryo induction. The treatment of 2,4-D (3,0 – 12 mg/l) used for callus induction. For embriogenic callus induction used 2,4-D (3,0 – 12,0 mg/l) combined with NAA 0,5 mg/l. The treatment of thidiazuron (0,1 – 0,7 mg/l) used for somatic embryo induction. The result showed that the treatment of 2,4-D 6,0 mg/l is the best for callus induction with compact of texture, green, dry and non embryogenic. The treatment of combination 2,4-D 12.0 mg/l with NAA 0.5 mg/l is the best for friable callus induction. The treatment of 2,4-D 6.0 mg/l combined with NAA 0,5 mg/l is the best for embryogenic callus induction with very friable of texture, easy to separate, dry, smooth and glossy. Thidiazuron of 0,1 mg/l treatment is the best for somatic embryos induction with the average number of 7,8 somatic embryos.